2008
DOI: 10.1515/hf.2008.133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autohydrolysis of Eucalyptus globulus wood on lignin structure. Part 2: Influence of autohydrolysis intensity

Abstract: Three different levels of autohydrolysis intensity, expressed as the prehydrolysis (P)-factor, were applied to Eucalyptus globulus wood at a liquor/wood ratio of 5:1. Lignin fractions were isolated from the wood residue as milled wood lignin (MWL), from the hydrolysate by centrifugation (insoluble fraction) and by ethyl acetate extraction (soluble fraction), and from the reactor wall as precipitate. With increasing autohydrolysis duration, a decrease in the content of aliphatic hydroxyl groups and of β-O-4 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 7 publications
6
77
0
1
Order By: Relevance
“…On the other hand, the lowest lignin content was determined from the black liquors, which were cooked from severely extracted wood (PHWE 2). As discussed above, enhanced delignification took place within a very narrow range of pre-treatment time, and significant decreases in lignin solubility and reactivity after harsh autohydrolysis conditions have been reported (Leschinsky et al 2008(Leschinsky et al , 2009Li, Gellerstedt 2008;Timilsena et al 2013;Zhu et al 2015). These observations were also in agreement with this study, as highly prolonged PHWE seemed to alter the structure of lignin in such a way that its dissolution was clearly hindered during the subsequent alkaline pulping.…”
Section: Analysis Of the Black Liquor Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the lowest lignin content was determined from the black liquors, which were cooked from severely extracted wood (PHWE 2). As discussed above, enhanced delignification took place within a very narrow range of pre-treatment time, and significant decreases in lignin solubility and reactivity after harsh autohydrolysis conditions have been reported (Leschinsky et al 2008(Leschinsky et al , 2009Li, Gellerstedt 2008;Timilsena et al 2013;Zhu et al 2015). These observations were also in agreement with this study, as highly prolonged PHWE seemed to alter the structure of lignin in such a way that its dissolution was clearly hindered during the subsequent alkaline pulping.…”
Section: Analysis Of the Black Liquor Propertiessupporting
confidence: 90%
“…Possible explanation could include, for example, various condensation reactions taking place during pretreatments, which rendered lignin structure insoluble and very resistant towards alkaline (but sulfur-free) cooking. This explanation was supported by previous studies (Leschinsky et al 2008;Li, Gellerstedt 2008;Timilsena et al 2013;Zhu et al 2015), in which a decreased delignification after harsh auto-hydrolysis conditions was observed. In these studies, it was also reported that the maximum extractability of lignin could be achieved within a very narrow range of reaction time, and a significant decrease in lignin solubility and reactivity was reported after harsh auto-hydrolysis conditions.…”
Section: Pulping Experimentssupporting
confidence: 86%
See 1 more Smart Citation
“…Recently some important studies in this area have been reported [7,9,13]. Our attempts in this direction include isolation of MWL (in accordance with the Björkman procedure [14] with minor modifications) from AW pre-extracted SM (SM_AW) and ESM [pre-extracted prior to ball-milling with AW, ESM_AW or dichloromethane (DCM), ESM_DCM].…”
Section: Introductionmentioning
confidence: 99%
“…Esse efeito caracteriza-se por aumentar a reatividade da lignina remanescente e assim dificultar o aproveitamento dos açúcares pela enzima aplicada posteriormente na etapa de sacarificação [31,32,33]. Em face dos resultados obtidos na hidrólise enzimática, sugere-se que essa consequência negativa foi detectada nos ensaios que sofreram deslignificação.…”
Section: Experimentos De Hidrólise Realizados Com Carga De Sólidos Deunclassified